University teachers’ experience of students interprofessional education: Qualitative contributions from teachers towards a framework - Frøydis Vasset; Atle Ødegård; Hans Petter Iversen; Synnøve Hofseth Almås; Elizabeth Willumsen; Susanne Lindqvist (Social Sciences and Humanities Open, 2023)
Background: Health and social care professionals need to be equipped to work together. Universities have a duty of care to their students to incorporate interprofessional education into the curricula. Here, we present findings from focus groups to delve deeper into the issues previously identified. Method: Three focus group interviews with teachers were conducted—two in Norway and one in the UK. Findings: We identified four themes: Organizational commitment. Values related to students’ interprofessional and collaborative practice. Professional identity and commitment to collaborative practice. Challenges with implementing interprofessional education. Discussion and conclusion: Educators continue to agree that interprofessional education is important, but the findings highlight the ongoing divide and uncertainty as to what to do and when to equip students for interprofessional collaboration. The educators call for the organization to show commitment and leadership so that stakeholders can come together to develop an Interprofessional education curriculum that students can sign up to. Time is of the essence, and a framework may help us here, especially if we can embrace the concept of social innovation and cocreate.